Natural Media in Islamic Religious Education ( at Purwakarta Nature School, West Java - Intan Julaikha; Sovani Rizky Handayani; Nurul Fadillah; Hanny Tri Yuniarti; Usep Setiawan (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2023)
Background of the problem Natural media is very important in Islamic Religious Education (PAI) lessons, the cost is not expensive and easy to get because they are around humans. The purpose of this study was to determine natural media in PAI at SD Alam Purwakarta, West Java. The methodology used is qualitative (narratively) data obtained through observation, interviews and documentation. The results of the study show that students attract more students' attention so that they can foster learning motivation Learning materials will have a clearer meaning so that they can be better understood by students and make it possible master and achieve learning objectives, so students are not bored students can do more learning activities because they not only listen to the educator's description, but also other activities such as observing, doing, demonstrating, PAI Lessons Faith, Worship, Al-Qur'an, Morals, Muamalah, Syari'ah, and Date/history, and builds IQ, EQ and Spiritual Intelligence for students. SD Alam Purwakarta West Java instills the values ​​of IKROM (Sincere, Kindness, Open Minded) and is strengthened by 4 Pillars which are morals, leadership, knowledge and entrepreneurship, and uses the SASS (Student Scount Natural School) program.